Pengaruh Penggunaan Model Pembelajaran Rotating trio exchange (RTE) Terhadap Kemampuan Kognitif Siswa Kelas VIII Pada Mata Pelajaran Pendidikan Agama Islam di SMPN 4 Klari Karawang - Nanda Agustin; Debibik Nabilatul Fauziah; Neng Ulya (Alifbata : Jurnal Pendidikan Dasar, 2025)
This study aims to find the effect of rotating trio exchange learning model on students' cognitive abilities. This research was conducted at SMPN 4 Klari Karawang in class VIII G as the experimental class and class VIII J as the control class in the subject of Islamic Religious Education. The method used in this research is a quantitative approach experimental method with a quasi-experimental design with a pretest and posttest group design. With a population of 412 students and samples taken in the study as many as 80 students. The increase in students' cognitive abilities can be seen from the increase in the average pretest and posttest results of the experimental class of 19.63, while in the control class it was 17.22. To see the effect of using the rotating trio exchange model on students' cognitive abilities can be seen from the results of the N-gain test calculation showing that the average N-gain value for the experimental class of 0.4330 has a moderate category with a percentage of 43%. Thus it can be concluded that there is a significant influence between the use of rotating trio exchange learning model on students' cognitive abilities.